Proteolytic activity in Serratia marcescens clinical isolates - Coria-Jiménez, R; Zárate-Aquino, C; Ponce-Ponce, O (Folia microbiologica, 2004)
Exoproteinase production was demonstrated in 64 clinical isolates of S. marcescens. A significant relationship was found between the site of origin (autopsy material, hemocultures, various other sources), proteinase activity, and LD50 of the analyzed isolates. The number of exoproteinases varied during a 14-h incubation in batch cultures; the most frequently found was a 57.5-kDa proteinase which was observed in all analyzed strains. The exoproteinase production was shown to be related to strain virulence.
Keywords: Virulence; exopeptidasy; Exopeptidases; Serratia marcescens; lidé; Humans; virulence